2011
DOI: 10.1093/eurjhf/hfq178
|View full text |Cite
|
Sign up to set email alerts
|

Urinary 8‐hydroxy‐2′‐deoxyguanosine reflects symptomatic status and severity of systolic dysfunction in patients with chronic heart failure

Abstract: In HF, urinary 8-OHdG seems to reflect the level of oxidative stress and various parameters related to symptomatic status and functional severity of CHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 41 publications
1
37
1
1
Order By: Relevance
“…Increased oxidative stress is detected in most types of HF, that resulting from ischaemic and non-ischaemic cardiomyopathy, pressure and volume overload, tachycardiomyopathy [9]. The side effects of oxidative stress in HF patients are vascular endothelial dysfunction [10], cardiac hypertrophy [11] and myocyte contractile dysfunction [12].…”
Section: Introductionmentioning
confidence: 99%
“…Increased oxidative stress is detected in most types of HF, that resulting from ischaemic and non-ischaemic cardiomyopathy, pressure and volume overload, tachycardiomyopathy [9]. The side effects of oxidative stress in HF patients are vascular endothelial dysfunction [10], cardiac hypertrophy [11] and myocyte contractile dysfunction [12].…”
Section: Introductionmentioning
confidence: 99%
“…42) Kobayashi, et al showed that urinary 8-OHdG was higher in heart failure patients than in control subjects, and that urinary 8-OHdG became higher as the NYHA class increased. 43) Moreover, there was a significant correlation between urinary 8-OHdG and cardiac functional parameters. BIOMARKERS IN HEART FAILURE Suzuki, et al measured serum 8-OHdG levels in 230 patients with chronic heart failure and 42 control subjects without heart failure by a sandwich ELISA.…”
Section: )mentioning
confidence: 91%
“…29 Recently, we reported that 8-OHdG is produced in failing cardiac tissue on the basis of sampling data from the coronary sinus and aortic root. 30 In addition, the urinary excretion of 8-OHdG is significantly correlated with clinical status and cardiac dysfunction in patients with CHF. 30 Thus, urinary (U) 8-OHdG may be a useful cardiac biomarker for evaluating oxidative stress at the cellular level and predicting the outcome of patients with CHF.…”
mentioning
confidence: 99%
“…30 In addition, the urinary excretion of 8-OHdG is significantly correlated with clinical status and cardiac dysfunction in patients with CHF. 30 Thus, urinary (U) 8-OHdG may be a useful cardiac biomarker for evaluating oxidative stress at the cellular level and predicting the outcome of patients with CHF. In the present study, we investigated whether U8-OHdG is a clinically useful biomarker for predicting the morbidity and mortality of patients with CHF compared with plasma BNP -the current gold standard biomarker for heart failure -and other neurohumoral factors.…”
mentioning
confidence: 99%